Factors Affecting Lawyers Adoption to Live Broadcast Platforms - Meng, Cai Zhi; Yusoff, Siti Khalidah, Mohd; Teo, Brian Sheng-Xian (International Journal of Emerging Trends in Social Sciences, 2022)
For many industries, live broadcasting is a free and efficient way to advertise. It has become a dedicated advertising channel for law firms to obtain clients. However, some platforms cannot provide reliable services for lawyers’ live broadcasting and their features are disappointing. In order to promote the live broadcast platform to better serve lawyers, this study tries to find out factors that influencing lawyers’ adoption of live broadcasting platforms. Unified Theory of Acceptance and Use of Technology (UTAUT) was extended by trust factor to form the research model. Survey was distributed among law firms in China and Smart-PLS was used to analyse research data. The empirical results indicated that all the factors were positively related to lawyers’ adoption to live broadcast platforms. The findings and recommendations aim to improve the cooperation efficiency between live broadcast platforms and lawyers, and increase the client acquisition rate of law firms.